The Effect of the Application of Biochar from Oil Palm Empty Bunches on the Growth of Falcataria moluccana - Rafly, Novendra Muhammad; Riniarti, Melya; Hidayat, Wahyu; Prasetia, Hendra; Wijaya, Bangun Adi; Niswati, Ainin; Hasanudin, Udin; Banuwa, Irwan Sukri (Journal of Tropical Upland Resources (J. Trop. Upland Res.), 2022)
Oil Palm Empty Fruit Bunches (OPEFB) waste is abundant and has become a problem. It can be applied as a promising biochar and will solve problems due to the large role of biochar as a soil amendment agent. The purpose of this study was to determine the application of biochar to increase the grow of F. moluccana. Biochar is produced by slow pyrolysis at a temperature of 400 ? and 600 ?. Biochar was applied to F. moluccana seedlings in plantations, with 3 doses (0 ton/ha, 25 ton/ha and 50 ton/ha) using a split plot research design with factorial Completely Randomized Design (CRD) as the basic design. Data analysis used Analysis of Variance (ANOVA) and carried out a further test of Least Significant Difference (LSD). Growth parameters height as increment, diameter increment and the growth rate were observed once a month for eight months. The results showed that the height increment and diameter increment of F. moluccana with the application of OPEFB biochar at dose of 50 tons / ha with pyrolysis temperature of 400 ? gave the best results for growth parameters compared to control plants. Based from the average growth rate per month application of 50 tons/ha with pyrolysis temperature of 400? shows the highest average, as well as the correlation between height and diameter increase is also the best.